Erratum to “The Effect of Using CIDR and Various Doses of PMSG as Well as Genistein on the Reproductive Characteristics of Palu Fat-tailed Sheep” - Mangun, Mardiah; Suyadi, Suyadi; Ihsan, Muhammad Nur; Marjuki, Marjuki (Jurnal Ilmu Ternak Universitas Padjadjaran, 2025)
This is a correction forDOI: https://doi.org/10.24198/jit.v22i1.38035In the originally published version of this article, the citation in column 1, page 15, line 11 from the bottom, … Suharto et al. (2008), does not appear in the References. Furthermore, the following references:Jainudeen, M., & Hafez, E. (1987). Reproductive failure in female. In E. Hafez (Ed.), Reproduction in Farm Animal (7th ed.). Lea and Febiger.andJainudeen, M. R., & Hafez, E. S. E. (1987). Gestation, Prenatal Physiology, and Parturition. In E. Hafez (Ed.), Reproduction in Farm Animal (7th ed.). Lea and Febiger.do not include letter codes (a and b) after the publication year.In this erratum we revise it accordingly.ReferencesJainudeen, M., & Hafez, E. (1987a). Reproductive failure in female. In E. Hafez (Ed.), Reproduction in Farm Animal (7th ed.). Lea and Febiger.Jainudeen, M. R., & Hafez, E. S. E. (1987b). Gestation, Prenatal Physiology, and Parturition. In E. Hafez (Ed.), Reproduction in Farm Animal (7th ed.). Lea and Febiger.Suharto, K., Junaidi, A., Kusumawati, A., & Widayati, D. T. (2008). Prediksi waktu ovulasi kambing Peranakan Etawah setelah disinkronisasi dengan controlled internal drug release jangka pendek. J. Indon. Trop. Agric. 33(2), 94 - 100.